Cross sectional study evaluating the correlation of thyroid dysfunction with severity of disease in rheumatoid arthritis - D., Vinoth Kumar; R., Aruna (International Journal of Research in Medical Sciences, 2020)
Background: The present study was conducted to evaluate the correlation of disease severity in RA and thyroid dysfunction. Methods: The present cross-sectional descriptive study enrolled 164 participants aged 12 years and above diagnosed as having RA. Use of drugs causing thyroid dysfunction, malignancy, diabetes mellitus, systemic hypertension, pregnancy and prior thyroidectomy were the criteria for exclusion. Data was analyzed using R and tests of significance were Chi square test and independent sample t-test and Pearson correlation. Institutional ethics committee approved the study and written informed consent was obtained from all study participants. Results: Serum TSH positively correlated with DAS 28 (r=0.2, p=0.005), ESR (r=0.2, p=0.03), CRP (r=0.2, p=0.006), RA factor (r=0.2, p=0.003), subjective assessment (r=0.3, p= 0.001) and anti TPO antibodies (r=0.7, p=0.001). Free T4 negatively correlated with DAS28 (r=-0.2, p=0.006), ESR (r=-0.2, p=0.02), CRP (r=-0.2, p=0.01). RA factor (r=-0.2, p=0.01), subjective assessment (r=-0.2, p= 0.01), anti TPO (r=-0.6, p=0.001) and Free T3 negatively correlated with DAS28 score (r=-0.2, p=0.02) , ESR (r=-0.2, p=0.03), RA factor (r=-0.3, p=0.001) and anti TPO antibodies (r=- 0.3, p=0.001). Conclusions: Hypothyroidism was significantly associated with disease severity of RA with linear positive correlation of TSH with DAS28 score, ESR, CRP, RA factor, subjective assessment and anti TPO antibodies, linear negative correlation of serum free T4 with DAS 28 score, ESR, CRP, RA factor, subjective assessment and anti TPO antibody and linear negative correlation of free T3 with DAS28 score, ESR, RA factor and anti TPO antibody was observed.